A percepção dos professores sobre o processo de inclusão escolar de alunos com deficiências no ensino regular da rede municipal de ensino de Porto Alegre - Medeiros, Maria Luiza Gomes (2015)
This research aims to understand the way teachers from regular schools from the Municipal Porto Alegre Net (RME) perceive the inclusion of students with disabilities, at school. This need rose along the walk of a researcher in the educacional Field, thus since she started her journey she always had inclusion´s students and this work always took into account the individulity of these subjects face to the consctruction of the knowledge. Entering the Master Course of Education, this student faced the same dificulty of other teachers in how to deal with inclusion´s students, this way rose the need of this study. The problem researched was the perception of the teachers in the schools RME of Porto Alegre before the process of school inclusion. This research was based on a qualitative approach, using a semi-structured interview as a data collection instrument; for the analysis of data was used for Analysis of Content. The paths of theoretical research discussed issues such as the Defectologia, the school inclusion, social development and cultural subjectivity. We also search in this research the subjective aspects which involve the teachers formation as well as the meaning of teaching for the interviewees. In this investigative way an interesting dialogue rose between school inclusion of students with disabilities and social inclusion. Along the journey we could notice teachers commited with educacional inclusion and interested in learning each time more for their students. In relation to the research findings, we can cite that mean teaching to the teachers interviewed is linked to the daily challenges they face and that permeates from lack of proper training to the shortage of human resources. However, they are happy with their work, given that sought training in inclusion that could support them to improve their educational services to students with disabilities.